O questionamento nos livros didáticos de Química do PNLD 2015 e 2018 - Jesus, Daniela Santos de (2018)
This study has the objective of verifying and analyzing the quality of the questions present in all collections of chemical textbooks approved in the PNLD of 2015 and 2018, the two periods were chosen due to this research being carried out during the period in which this transition occurred. As we wanted to have an initial idea of the characteristics of the collections we realized only with the volume 1 of each one of them and also because the volumes have very similar characteristics. To verify the questions, we constructed categories that sought to identify the location of the questions, the context of incidence and the acceptance of the diversity of response for each questioning based on the classification of Leite et.al. (2012). In order to analyze the quality of the questions, we base ourselves on indicators constructed by Neri-Souza (2006) as information, consolidation, exploration, elaboration, synthesis and evaluation, which indicate the quality of the questions, showing when a question tends to have character confirmation or conversion. The results show that the textbooks of chemistry present, predominantly, questions at the end of the sections, with high incidence of questions about school science and acceptance of a relative diversity of answers. In relation to quality, it was verified that, in the questions of the textbooks of chemistry, it is low, that is, the majority of the questions are information and exploration questions, with few questions with synthesis and evaluation. And, in the comparison between the collections of the PNLD 2015 and 2018, the questions did not undergo major modifications, thus presenting very close profiles.